Early diagnosis of cancer: systems approach to support clinicians in primary care. (9th February 2023) - Black, Georgia B; Lyratzopoulos, Georgios; Vincent, Charles A; Fulop, Naomi J; Nicholson, Brian D
Abstract : Georgia Black and colleagues argue that rather than focusing on the initial consultation efforts to reduce diagnosis times should look at the wider system